(untitled) (Academia Journal of Medicine, 2023)
The field of dentistry goes beyond the skills of dental professionals alone. Collaborative efforts among different healthcare providers are crucial for comprehensive patient care. One such critical role is played by pharmacists in dentistry. Pharmacists bring their expertise in medications and their interactions to ensure the safe and effective use of drugs prescribed by dentists. In this article, we will discuss the vital contributions of pharmacists in dental care and their role in promoting oral health.